Metallopanstimulin-1 (MPS-1) mediates the promotion effect of leptin on colorectal cancer through activation of JNK/c-Jun signaling pathway - Cao, Dongxing (Cell Death Dis, 2019)
Obesity is a major epigenetic cause for colorectal cancer (CRC). Leptin is implicated in obesity-associated CRC, but the underlying mechanism remains unclear. The current study identified over-expression of metallopanstimulin-1 (MPS-1) in CRC patients through microarray and histological analysis, especially in obese CRC patients. MPS-1 was correlated with advanced tumor stage, suggesting its association with CRC progression. In addition, MPS-1 over-expression was associated with poor overall survival (OS) in obese CRC patients, but not in their non-obese counterparts, suggesting its potential as a prognostic marker of obese CRC patients. MPS-1 expression was positively associated with circulating leptin levels in CRC patients, especially in obese cases. Functional experiments demonstrated that MPS-1 silencing inhibited tumor proliferation and colony formation, and induced apoptosis of CRC cells in vitro. Converse results were obtained from the experiments with MPS-1 over-expression. Mechanistically, MPS-1 executed its action through induction of c-Jun N-terminal kinase (JNK)/c-Jun pathway. Moreover, the promotion effect of MPS-1 on CRC progression was modulated by leptin. In vivo studies demonstrated that MPS-1 silencing suppressed tumor growth of CRC via inhibiting JNK/c-Jun signaling. Collectively, this study indicates that MPS-1 promotes leptin-induced CRC via activating JNK/c-Jun pathway. MPS-1 might represent a potent candidate for the treatment and prognostic prediction of obesity-associated CRC.